Pemanfaatan Mixed Method dalam Studi Kasus Inovasi Pembelajaran Matematika di Era Digital - Sidabutar, Natalia ayu; Retno Windasari; Izwita Dewi; Edy Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has driven various innovations in mathematics education, such as flipped classroom, blended learning and the use of interactive applications. However, the implementation of these innovations does not always run smoothly due to challenges like limited technological access, teacher readiness, and student adaptation. Therefore, a comprehensive research approach is needed to explore these phenomena in depth. This study employs a mixed method approach through a literature review to examine the effectiveness of digital-based mathematics learning innovations and identify the challenges encountered during implementation. The findings from several studies published in the last five years show that mixed method research provides a more comprehensive picture of students’ learning processes and outcomes, as well as deeper insights into the factors that influence the success of educational innovations. Thus, this approach serves as a valuable foundation for designing adaptivem effective and sustainable mathematics learning strategies in digital era.